2009
DOI: 10.1097/mjt.0b013e3181921188
|View full text |Cite
|
Sign up to set email alerts
|

Divalproex Sodium-Induced Eosinophilic Pleural Effusion

Abstract: Eosinophilic pleural effusion is defined as an effusion in which eosinophils constitute more than 10% of white blood cells. These effusions can be due to multiple causes with drugs being implicated as one of the etiological agents. We report a case of 48-year-old woman with seizure disorder on divalproex sodium (Depakote) who presented with dyspnea. A chest radiograph demonstrated right pleural effusion. Investigations showed peripheral blood eosinophilia with thoracocentesis revealing eosinophilic exudative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Through literature research, we collected 18 published cases of valproic acid-associated pleural effusion, aging from 15 to 70 years. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Ten of the cases were male. Daily dosage differed among cases, from 250 to 2000 mg, the majority over 1000 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through literature research, we collected 18 published cases of valproic acid-associated pleural effusion, aging from 15 to 70 years. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Ten of the cases were male. Daily dosage differed among cases, from 250 to 2000 mg, the majority over 1000 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is thought to be mediated via increasing the inhibitory action of gamma-aminobutyric acid 1 . The commonly observed side effects are tremors, dizziness, weight gain, nausea, hair loss and, and others 2–4 …”
mentioning
confidence: 99%
“…When diagnosed with drug-induced effusion, and if the patient's clinical condition permits, the patient can be expected to recover spontaneously. However, there is not enough evidence on whether to re-start the drug or not 4 . As PE in our case continued for three months, the drug was discontinued, and then the PE regressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that pleural effusion (PE) may rarely occur due to the use of VPA 3 . In the literature, 13 cases of PE developing due to the use of VPA have been reported so far [1][2][3][4][5][6][7][8][9][10][11] . In an animal study investigating teratogenic effect of VPA, the development of drug-induced PE has also been reported 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some drugs used in psychiatry and neurology are some of the most important, including valproic acid (and its derivatives) and dantrolene [5][6][7][8]. EPE was also reported as a complication of treatment with tazinidine, trimipramine and fluoxetine [9][10][11].…”
Section: Drug-induced Eosinophilic Pleural Effusionmentioning
confidence: 99%